What makes customer satisfied? investigating the role of restaurant attributes at Malay food restaurants/ Muhammad ‘Arif Aizat Bashir ... [et al.] - Bashir, Muhammad ‘Arif Aizat; Abd Majid, Hairul Nizwan; Norkhalid, Nurul Adibah; Mohd Zahari, Mohd Salehuddin; Ismail, Hazmal (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Undoubtedly, promoting business retention through customer satisfaction is crucial, especially in the highly demanding restaurant sectors. Therefore, restaurateurs must address the significant factors that may increase customer satisfaction to assure the success of a restaurant, including Malay food restaurants, without exception. Therefore, this research aims to determine the relationship between restaurant attributes and its dimensions of food quality, restaurant atmospheric, and service quality that potentially influences customer satisfaction at Malay food restaurants in Malaysia. The primary data was obtained using a survey questionnaire, with 384 sets of questionnaires have been distributed to individuals who have visited Malay food restaurants. Data were analysed, and the study’s key findings were reviewed to understand the relationship between restaurant attributes of food quality, restaurant atmospheric, and service quality with customer satisfaction. From the results, all these elements play a pivotal role in determining customer satisfaction. This study found that key aspects of the restaurant attributes, namely the food quality, restaurant atmosphere, and service quality, have significant relationships with customer satisfaction, with different strengths of correlation between them.